Selective fluorination of Fc glycans enhances antibody-mediated effector functions - Xianyang Wang; Margaryta Gomozkova; Siqi Li; Biswarup Banerjee; Guanghui Zong; Dominique Missiakas; Lai-Xi Wang (Proceedings of the National Academy of Sciences, 2026)
Antibody effector functions such as antibody-dependent cellular cytotoxicity (ADCC) and various complement-dependent activities are critically influenced by the structure and composition of Fc N-glycans. Terminal galactosylation is generally associated with enhanced FcγRIIIA binding and C1q recruitment, thereby improving antibody activities. Recent structural studies suggest that terminal galactose can restrict glycan flexibility and stabilize Fc conformation by interacting with CH2 domain residues, thereby reducing the entropic penalty for FcγRIIIA binding. Motivated by this structural insight, we hypothesized that fine-tuning galactose-mediated Fc glycan-Fc domain interactions via site-selective fluorination could further modulate Fc-receptor and Fc–complement interactions. To test this, we developed a chemoenzymatic glycoengineering approach to generate homogeneous antibodies bearing precisely fluorinated Fc N-glycans. Key to this strategy was the chemical synthesis of position-specific fluorinated full-length Fc glycans, which were subsequently installed onto the antibody via enzymatic Fc glycan remodeling catalyzed by a glycosynthase mutant. Using this platform, we constructed a panel of homogeneous fluorinated antibodies and evaluated their functional consequences. ELISA-based binding assays revealed that fluorination at the C2 or C6 position of terminal galactose significantly increased FcγRIIIA affinity. Corresponding enhancements in ADCC were confirmed using a cell-based reporter bioassay. Furthermore, fluorination at these positions also promoted C1q binding and elevated the antibody-dependent cellular phagocytosis potency in whole blood assays. These results collectively demonstrate that selective Fc glycan fluorination represents a unique strategy to enhance antibody effector functions, providing a paradigm for precision glycoengineering in antibody therapeutics.